2006
DOI: 10.1007/s10875-006-9038-y
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to Mitotic Apparatus: Association with Other Autoantibodies and Their Clinical Significance

Abstract: The most important mitotic apparatus (MA) antigens are centrosome (CE), nuclear mitotic apparatus (NuMA-1, NuMA-2), midbody, and centromere F (CENP-F). We studied associations of anti-MA antibodies with other autoantibodies and their clinical significance. A total of 6270 patients were studied for the presence of anti-MA antibodies on HEp-2 cells. Sera positive for anti-MA were tested for anti-extractable nuclear antigens (ENA) antibodies. Anti-MA antibodies were detected in 56 (45 females and 11 males) of 627… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Patients with PBC seropositive for ACA often seem to develop portal hypertension 7 or liver failure 8 . ACA is occasionally found in the sera of patients with type 1 autoimmune hepatitis (AIH) 2,5,6,9,10 or even in the sera of patients with hepatitis C virus (HCV)‐related chronic liver disease (CLD) 11,12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with PBC seropositive for ACA often seem to develop portal hypertension 7 or liver failure 8 . ACA is occasionally found in the sera of patients with type 1 autoimmune hepatitis (AIH) 2,5,6,9,10 or even in the sera of patients with hepatitis C virus (HCV)‐related chronic liver disease (CLD) 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…8 ACA is occasionally found in the sera of patients with type 1 autoimmune hepatitis (AIH) 2,5,6,9,10 or even in the sera of patients with hepatitis C virus (HCV)-related chronic liver disease (CLD). 11,12 We have previously shown that patients with AIH seropositive for ACA are likely to have milder liver damage and a more favorable prognosis. 13 However, a case report indicating that an AIH patient associated with CREST syndrome, who rapidly developed hepatic failure, was later documented.…”
Section: Introductionmentioning
confidence: 99%
“…Anti‐MSA antibodies are reported to be associated with a wide variety of autoimmune diseases including RA, SS, SLE, MCTD, polyarteritis nodosa, polymyositis, and Hashimoto's thyroiditis . Our study revealed that 72.7% (16/22) of anti‐MSA‐positive patients in Chinese had autoimmune CTDs, mostly SS, RA, and SLE.…”
Section: Discussionmentioning
confidence: 59%
“…To date, there have been very few reports on patients with HCV-related CLD seropositive for ACA [25,40]. To the best of our knowledge, this is the first study that has carried out detailed analyses of clinical parameters in patients with HCV-related CLD seropositive for ACA.…”
Section: Discussionmentioning
confidence: 96%